KEDUDUKAN DAN AKIBAT HUKUM AKTA WASIAT YANG TIDAK DIKETAHUI AHLI WARIS DALAM HUKUM WARIS PERDATA - Taqiyyah Aisyah; Rr Shafa Camila; Bintang Firmansyah (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
A will plays a crucial role in the distribution of a person's estate after death. However, problems arise when the will is unknown to the heirs at the time of inheritance distribution based on civil law (ab-intestato). This research aims to analyze the legal status of a will unknown to the heirs and to explain the legal implications if the will is found after the inheritance has been distributed. Using a normative juridical method and a legislative approach, this study examines the legal standing of a valid will even if it is unknown to the heirs. The findings indicate that the discovery of a will after the distribution of inheritance can result in the cancellation or redistribution of assets according to the will's contents. Heirs who feel disadvantaged have the right to file a legal claim to enforce their rights. In conclusion, an unknown will remains legally binding, and the inheritance distribution can be revoked or altered to comply with the will. Therefore, examining the existence of a will before inheritance distribution is highly recommended to avoid future disputes.